Hardware Prototyping and Modelling of Prototype Filter for FBMC - Calisir, Bircan; Akbal, Ayhan (Wiley-Hindawi, 2020)
Filter bank multicarrier (FBMC) is one of the effective candidates for the fifth generation of wireless communication networks. 5G (5th-generation wireless systems) is accepted as the next major stage of mobile telecommunication technology. The extent of 5G will be expanded mobile broadband services to next-generation automobiles and connected machines. In particular, filter bank multicarrier with offset quadrature amplitude modulation (FBMC/OQAM) is determined as the future generation 5G air interface by researchers recently. Filter bank multicarrier (FBMC) is admitted as one of the alternative technologies for multicarrier modulation. Compared to orthogonal frequency-division multiplexing (OFDM), FBMC has better spectrum shape and supports mobility. Therefore, efficient hardware implementations have highly interested researchers. Cyclic prefix (CP) and guard band are used for orthogonal frequency-division multiplexing (OFDM) and this causes loss of spectral efficiency, but FBMC applications do not need CP and guard band. Due to the fact that FBMC has offset QAM (OQAM) and band-limited filtering features on each subcarrier, the need for CP and guard band is eliminated. In this paper, novel pipelined hardware architecture of the filter design of FBMC/OQAM modulator has been proposed.
Keywords: Design